Cash flow for dummies - Tracy, Tage C.; Tracy, John A. (Hoboken, N.J. : John Wiley [distributor], 2012)
This hands-on guide is your plain-English manual to cash flow basics. You'll get valuable tips, techniques, and information on the fundamentals of cash management to maximize cash flow and understand how it affects the quality of your company's earnings.
Fitting cash flow into the big picture of running a business -- Using financial statements to assess cash health -- Getting intimate with your company's cash flow needs -- Managing your business with cash flow in mind -- The part of tens.
Includes index.
Keywords: Business enterprises -- Finance; Small business -- Finance; Cash management